Letter from Adele Leopold - Adele Leopold:::::: (1968)
A letter from Adele Leopold that congratulates a State Committee member on their appointment and asks for support in her campaign for State Women's Chairman of the Democratic State Central Committee. She pledges to devote her full energy to strengthening the Democratic Party, emphasizing the importance of engaging new volunteers energized by recent primary campaigns. Leopold expresses her commitment to building a viable and active party organization in California and hopes to secure the recipient's vote at the upcoming Sacramento meeting. The attached political résumé outlines her experience in party leadership roles, legislative work, campaign involvement, and service within the Democratic State Central Committee.